2012
DOI: 10.1097/sle.0b013e318270473b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity and Associated Diseases on Outcome After Laparoscopic Cholecystectomy

Abstract: Obesity is a risk factor for operative treatment. This study examined the impact of obesity and associated comorbidities on complications after laparoscopic cholecystectomy (LC). Altogether, 1581 consecutive patients with symptomatic gallstones underwent LC between the years 1995 and 2008. Preoperative data and operative outcome of the 437 obese patients [302 with body mass index (BMI) 30 to 35 kg/m² and 135 with BMI ≥ 35.1 kg/m²] and 1144 nonobese controls (BMI ≤ 29.9 kg/m²) undergoing LC were compared. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
6
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 23 publications
3
32
6
2
Order By: Relevance
“…Our incisional hernia rate is much lower than that in the reported literature for single incision LC [18][19][20][21][22]. Obesity has been shown to be an independent risk factor for both surgical site infection and incisional umbilical hernia formation [6,8,23]. We believe that closure under direct visualization and loose approximation of the skin has led to proper fascial closures and decreased risk of wound infection in our patients.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Our incisional hernia rate is much lower than that in the reported literature for single incision LC [18][19][20][21][22]. Obesity has been shown to be an independent risk factor for both surgical site infection and incisional umbilical hernia formation [6,8,23]. We believe that closure under direct visualization and loose approximation of the skin has led to proper fascial closures and decreased risk of wound infection in our patients.…”
Section: Discussioncontrasting
confidence: 77%
“…According to a study from the Center for Disease Control and Prevention, 35.9% of Americans are considered obese with a BMI 4 30 kg/m 2 with 17.4% of those having BMI 4 35 [5]. A BMI 4 30 is associated with a 3-fold increase in the incidence of cholelithiasis and biliary disease and diabetes carries a 1.9-fold increased risk [6][7][8]. Surgeons are continually challenged with the task of operating on an increasing number of high-risk patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Obese patients undergoing LC have an eightfold higher risk of CTO than non-obese patients (OR = 7.6; 95% CI: 4.1-14; P < 0.001) [52]. Compared to the nonobese patients, class I and class II-III obese patients have a two-and threefold increase in the risk of CTO (OR = 1.8; 95% CI: 1.1-2.8; P = 0.0105) and (OR = 2.7; 95% CI: 1.5-4.6; P = 0.0006), respectively [53].…”
Section: Actual Problems Of Emergency Abdominal Surgerymentioning
confidence: 94%
“…8,[11][12][13] Previous studies have shown similar rates of postoperative complications in obese and nonobese groups. 7,[14][15][16][17][18][19][20][21] Indeed, the only consistent difference between the groups has been increased operating time.…”
mentioning
confidence: 99%